(untitled) (Bangladesh Medical Journal, 2026)
Stroke in young adults has substantial clinical and socioeconomic consequences, particularly in low- and middle-income countries where cardiac disorders may remain undiagnosed until the index cerebrovascular event. The study aimed to determine the pattern of stroke, frequency of selected cardiac disorders, and their association with ischemic and hemorrhagic stroke among young adults in Bangladesh. This hospital-based analytical cross-sectional study was conducted in the Medicine Ward of Jahurul Islam Medical College Hospital, Kishoreganj, from September 2020 to February 2021. A total of 100 consecutive patients aged 18-50 years with radiologically confirmed stroke were enrolled. Socio-demographic characteristics, stroke subtype, electrocardiographic (ECG) and echocardiographic findings, and cardiac disorders were analyzed. Associations were tested using Chi-square analysis, and logistic regression was used to estimate odds ratios (ORs) with 95% confidence intervals (CIs). The mean age was 42.09 ± 7.14 years; 57% were aged 42-50 years, and 31% were aged 34-41 years. Males constituted 74% of patients, with a male-to-female ratio of 2.85:1. Socioeconomic findings showed that 96% were married, 68% had no formal or below-secondary education, 37% were in other occupations, 22% were businesspersons, 16% were housewives, 74% earned 20,000 BDT or less per month, and 79% lived in urban areas. Ischemic stroke predominated in 81% of cases. In comparison, hemorrhagic stroke accounted for 19%, giving an ischemic-to-hemorrhagic ratio of approximately 4.3:1. ECG abnormalities were significantly more frequent in ischemic than hemorrhagic stroke (63.0% vs. 26.3%, p = 0.004). St-elevation infarction patterns occurred only in ischemic cases (23.5%). Abnormal echocardiographic findings were more common in hemorrhagic stroke (68.4% vs. 43.2%, p = 0.04). Coronary artery disease (CAD) was the most frequent (43.0%) cardiac disorder (48.1% vs. 21.1%; χ² = 4.610, p = 0.032), and Valvular heart disease (VHD) was present in 16.0% overall (19.8% vs. 0.0%; χ² = 4.468, p = 0.035); both were significantly associated with ischemic stroke. Congenital heart disease (CHD) was present in 19.0% overall and showed the strongest association with hemorrhagic stroke (63.2% vs. 8.6%; χ² = 29.720, p < 0.001). Logistic regression confirmed CAD (OR = 1.23, 95% CI: 1.01-1.56) and VHD (OR = 1.29, 95% CI: 1.05-1.62) as predictors of ischemic stroke, and CHD (OR = 7.31, 95% CI: 3.12-17.12) as a strong predictor of hemorrhagic stroke. Atrial fibrillation, left ventricular failure, cardiogenic thrombus, and single or multiple cardiac disease patterns did not differ significantly by stroke subtype. Coronary artery disease and valvular heart disease were linked to ischemic stroke, whereas congenital heart disease strongly predicted hemorrhagic stroke among young stroke patients. Routine ECG and echocardiography should be emphasized in young adults presenting with stroke to improve etiological classification, secondary prevention in Bangladesh. Bangladesh Med J. 2025 Sept; 54(3): 16-23